Determinação simultânea de parabenos em adoçantes usando técnicas voltamétricas e calibração de segunda ordem - Dantas, Maria do Socorro Ribeiro (2021)
Parabens are esters derived from 4-hydroxybenzoic acid such as methylparaben (MeP), ethylparaben (EtP), propylparaben (PrP), butylparaben (BuP) and benzylparaben (BzP). They are chemical preservatives widely used in cosmetics, pharmaceuticals and foodstuffs, with permitted use in the European Union and also in Brazil, according to legislation of the National Health Surveillance Agency - RDC Resolution No. 162 of September 11, 2001, establishing a maximum concentration allowed for 0,4% individual per ester and 0,8% for mixtures the esters in products of personal hygiene, cosmetics and perfumes. Exposure of people to parabens occurs due to rapid absorption of the skin (cosmetics) as well as in the gastrointestinal tract and blood (medicines and food), endocrine disrupting effect, causing hormonal changes, in addition to being carcinogenic. This work aims to simultaneously determine MeP, EtP; PrP and BuP in artificial sweeteners using glassy carbon electrode by square wave voltammetry associated with second order calibration. The response potential and sensitivity vary with the change in the pH of the medium, greater sensitivity in Britton Robunson buffer (pH = 4.5) range with linear response from 0.78 to 4.48 μmol L-1 LOD and LOQ of 0, 017 μ mol L-1 and 0.0581 μmol L-1 , respectively. Calibration models were constructed for each analyte using split squares with residual bilinearization (U-PLS / RBL) and multivariate curve resolution with alternating squares (MCR-ALS). The models were evaluated using a validation set (16 mixtures) obtained from a Taguchi design, presenting a Relative Error Prediction range ranging from 3.30% to 3.88% and 5.70% to 7.60% , respectively. Finally, the U-PLS/RBL and MCR-ALS calibration models were applied to nine samples of sweeteners, demonstrating a great analytical performance and achieving the second order advantage, with a range of recoveries ranging from 82.6% to 121 % and 83,0% to 123% respectively. Thus, the proposed method proved to be an effective and unprecedented alternative for the simultaneous analysis of parabens in sweeteners.